Exploring -ING Forms in the Novel Words Adulting, Trolling, and Social Distancing - Jimenez, Melanie (Papanda Publisher, 2025)
This paper investigates the productivity of words ending in -ing through exploring three novel examples namely: adulting, social distancing, and trolling. Through the use of corpus-based methodologies using the NOW corpus, the study determined the semantic meaning of the selected novel words through collocations and identified the syntactic behavior and functions of -ing in each word by utilizing an automated part-of-speech (POS) tagger. This study aims to answer the following questions: 1) What is the semantic meaning of adulting, trolling, and social distancing in Philippine context and 2) what are the syntactic functions of ‘-ing’ in adulting, trolling, and social distancing. Part of the discussion is determining the pedagogical implications of the results of the study in language teaching and learning and identifying any grammatical feature associated with the use of adulting, trolling, and social distancing that may be of significance to Philippine English.